Scoping the applicability of the KOC concept for pesticides across soil particle size and carbon content - Marija Gadžimuradova; Gabriel Sigmund; Valentina Sechi; Peter van der Maas; Nora B. Sutton (Environmental Pollution, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

MicroNIR spectroscopy with chemometric analysis provides rapid protein content evaluation and prediction of semi-refined flaxseed protein extract produced via pulsed electric field (PEF)-assisted extraction - Jervee M. Punzalan; Peter Hartono; Sara J. Fraser-Miller; Sze Ying Leong; Kevin Sutton; Gert-Jan Moggre; Keith C. Gordon; Indrawati Oey (Food Chemistry, 2025)

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Soil-based carbon farming: Opportunities for collaboration - Alex Baumber; Rebecca Cross; Peter Ampt; Cathy Waters; Jennifer Ringbauer; Isabella Bowdler; Amanda Scott; Lorraine Gordon; Andres Sutton; Graciela Metternicht (Journal of Rural Studies, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Observing the full ocean volume using Deep Argo floats - Nathalie V. Zilberman; Virginie Thierry; Brian King; Matthew Alford; Xavier André; Kevin Balem; Nathan Briggs; Zhaohui Chen; Cécile Cabanes; Laurent Coppola; Giorgio Dall’Olmo; Damien Desbruyères; et al. (Frontiers in Marine Science, 2023)
The ocean is the main heat reservoir in Earth’s climate system, absorbing most of the top-of-the-atmosphere excess radiation. As the climate warms, anomalously warm and fresh ocean waters in the densest layers formed near Antarctica spread northward through the abyssal ocean, while successions of warming and cooling events are seen in the deep-ocean layers formed near Greenland. The abyssal warming and freshening expands the ocean volume and raises sea level. While temperature and salinity characteristics and large-scale circulation of upper 2000 m ocean waters are well monitored, the present ocean observing network is limited by sparse sampling of the deep ocean below 2000 m. Recently developed autonomous robotic platforms, Deep Argo floats, collect profiles from the surface to the seafloor. These instruments supplement satellite, Core Argo float, and ship-based observations to measure heat and freshwater content in the full ocean volume and close the sea level budget. Here, the value of Deep Argo and planned strategy to implement the global array are described. Additional objectives of Deep Argo may include dissolved oxygen measurements, and testing of ocean mixing and optical scattering sensors. The development of an emerging ocean bathymetry dataset using Deep Argo measurements is also described.

Observed amplification of the seasonal CO2 cycle at the Southern Ocean Time Series - Elizabeth H. Shadwick; Cathryn A. Wynn-Edwards; Richard J. Matear; Peter Jansen; Eric Schulz; Adrienne J. Sutton (Frontiers in Marine Science, 2023)
The Subantarctic Zone, the circumpolar region of the Southern Ocean between the Subtropical and Subantarctic fronts, plays an important role in air-sea CO 2 exchange, the storage of anthropogenic CO 2 , and the ventilation of the lower thermocline. Here we use a time series from moored platforms deployed between 2011 and 2021 as part of the Southern Ocean Time Series (SOTS) observatory to investigate the seasonality and interannual variability of upper ocean hydrography and seawater CO 2 partial pressure (pCO 2 ). The region is a net sink for atmospheric CO 2 over the nearly 10-year record, with trends revealing that the ocean pCO 2 may be increasing slightly faster than the atmosphere, suggesting that oceanic as well as anthropogenic atmospheric forcing contributes to the decadal change, which includes a decline in pH on the order of 0.003 yr −1 . The observations also show an amplification of the seasonal cycle in pCO 2 , potentially linked to changes in mixed layer depth and biological productivity.

Subantarctic pCO2 estimated from a biogeochemical float: comparison with moored observations reinforces the importance of spatial and temporal variability - Cathryn Ann Wynn-Edwards; Elizabeth H. Shadwick; Peter Jansen; Christina Schallenberg; Tanya Lea Maurer; Adrienne J. Sutton (Frontiers in Marine Science, 2023)
Understanding the size and future changes of natural ocean carbon sinks is critical for the projection of atmospheric CO 2 levels. The magnitude of the Southern Ocean carbon flux has varied significantly over past decades but mechanisms behind this variability are still under debate. While high accuracy observations, e.g. from ships and moored platforms, are important to improve models they are limited through space and time. Observations from autonomous platforms with emerging biogeochemical capabilities, e.g. profiling floats, provide greater spatial and temporal coverage. However, the absolute accuracy of CO 2 partial pressure ( p CO 2 ) derived from float pH sensors is not well constrained. Here we capitalize on data collected for over a year by a biogeochemical Argo float near the Southern Ocean Time Series observatory to evaluate the accuracy of p CO 2 estimates from floats beyond the initial in water comparisons at deployment. A latitudinal gradient of increasing p CO 2 southward and spatial variability contributed to observed discrepancies. Comparisons between float estimated p CO 2 and mooring observations were therefore restricted by temperature and potential density criteria (~ 7 µatm difference) and distance (1° latitude and longitude, ~ 11 µatm difference). By utilizing high quality moored and shipboard underway p CO 2 observations, and estimates from CTD casts, we therefore found that over a year, differences in p CO 2 between platforms were within tolerable uncertainties. Continued validation efforts, using measurements with known and sufficient accuracy, are vital in the continued assessment of float-based p CO 2 estimates, especially in a highly dynamic region such as the subantarctic zone of the Southern Ocean.

Lichens as spatially transferable bioindicators for monitoring nitrogen pollution - Jay Delves; Jason E.J. Lewis; Niaz Ali; Saeed A. Asad; Sudipto Chatterjee; Peter D. Crittenden; Matthew Jones; Aysha Kiran; Bishnu Prasad Pandey; David Reay; Subodh Sharma; Dendup Tshering; et al. (Environmental Pollution, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Comparative biology of the grenadiers Macrourus caml and M. whitsoni in the Ross Sea region, Antarctica - Bradley R. Moore; Steven J. Parker; Peter M. Marriott; Colin Sutton; Matthew H. Pinkerton (Frontiers in Marine Science, 2022)
The grenadiers Macrourus caml and M. whitsoni form a significant bycatch component of longline fisheries for Antarctic toothfish ( Dissostichus mawsoni ) in the Southern Ocean. A lack of species-level biological and catch data has to date hindered the development of quantitative assessments for these deepwater species. This paper examines species- and sex-specific life histories of M . caml and M . whitsoni in the Ross Sea region, Antarctica, from samples collected from the commercial fishery and research collections. Macrourus caml was found to live longer, grow slower, and attain a larger maximum length than M . whitsoni , reaching at least 65 years of age and 97 cm total length (TL) vs. 43 years and 78 cm TL for M . whitsoni . In addition, M . caml attains a larger length for a given age and a greater weight for a given length. For each species, females of a given age were larger and reached a greater maximum age than males. Assuming that selectivity of the fishing gear is related to fish size, greater fishing pressure on females than males is likely, and was evidenced by female-biased sex ratios of both species. Estimates of natural and fishing mortality rates were low for both species. Despite having a shorter lifespan and attaining a smaller maximum length, M . whitsoni matured later in life and at larger lengths than M . caml . Although sampling opportunities are constrained seasonally due to sea ice cover, gonad staging and interannual patterns in gonadosomatic indices suggest prolonged spawning for both species, with available data indicating peak spawning during austral summer. The differences in life history observed between these two closely related and morphologically similar species illustrates the importance of understanding species-specific life histories to infer responses to exploitation, provide key biological inputs to inform parameters for future risk assessments and ecosystem models as well as baseline information for comparative work over both time and space, contribute to greater clarity in managing fisheries that interact with these two species, and further our understanding of grenadier life history.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Changes in Southern Ocean Biogeochemistry and the Potential Impact on pH-Sensitive Planktonic Organisms - Elizabeth Shadwick; Andrés Rigual-Hernández; Ruth Eriksen; Peter Jansen; Diana Davies; Cathryn Wynn-Edwards; Adrienne Sutton; Christina Schallenberg; Thomas Trull (Oceanography, 2021)

Synergistic effects of harvest and climate drive synchronous somatic growth within key New Zealand fisheries - John R. Morrongiello; Peter L. Horn; Caoimhghin Ó Maolagáin; Philip J. H. Sutton (Global Change Biology, 2021)
Fisheries harvest has pervasive impacts on wild fish populations, including the truncation of size and age structures, altered population dynamics and density, and modified habitat and assemblage composition. Understanding the degree to which harvest‐induced impacts increase the sensitivity of individuals, populations and ultimately species to environmental change is essential to ensuring sustainable fisheries management in a rapidly changing world. Here we generated multiple long‐term (44–62 years), annually resolved, somatic growth chronologies of four commercially important fishes from New Zealand's coastal and shelf waters. We used these novel data to investigate how regional‐ and basin‐scale environmental variability, in concert with fishing activity, affected individual somatic growth rates and the magnitude of spatial synchrony among stocks. Changes in somatic growth can affect individual fitness and a range of population and fishery metrics such as recruitment success, maturation schedules and stock biomass. Across all species, individual growth benefited from a fishing‐induced release of density controls. For nearshore snapper and tarakihi, regional‐scale wind and temperature also additively affected growth, indicating that future climate change‐induced warming and potentially strengthened winds will initially promote the productivity of more poleward populations. Fishing increased the sensitivity of deep‐water hoki and ling growth to the Interdecadal Pacific Oscillation (IPO). A forecast shift to a positive IPO phase, in concert with current harvest strategies, will likely promote individual hoki and ling growth. At the species level, historical fishing practices and IPO synergized to strengthen spatial synchrony in average growth between stocks separated by 400–600 nm of ocean. Increased spatial synchrony can, however, increase the vulnerability of stocks to deleterious stochastic events. Together, our individual‐ and species‐level results show how fishing and environmental factors can conflate to initially promote individual growth but then possibly heighten the sensitivity of stocks to environmental change.

Men’s experiences of radiotherapy treatment for localized prostate cancer and its long-term treatment side effects: a longitudinal qualitative study - E. Sutton; J. A. Lane; M. Davis; E. I. Walsh; D. E. Neal; F. C. Hamdy; M. Mason; J. Staffurth; R. M. Martin; C. Metcalfe; T. J. Peters; J. L. Donovan; et al. (Cancer Causes & Control, 2021)
Purpose To investigate men’s experiences of receiving external-beam radiotherapy (EBRT) with neoadjuvant Androgen Deprivation Therapy (ADT) for localized prostate cancer (LPCa) in the ProtecT trial. Methods A longitudinal qualitative interview study was embedded in the ProtecT RCT. Sixteen men with clinically LPCa who underwent EBRT in ProtecT were purposively sampled to include a range of socio-demographic and clinical characteristics. They participated in serial in-depth qualitative interviews for up to 8 years post-treatment, exploring experiences of treatment and its side effects over time. Results Men experienced bowel, sexual, and urinary side effects, mostly in the short term but some persisted and were bothersome. Most men downplayed the impacts, voicing expectations of age-related decline, and normalizing these changes. There was some reticence to seek help, with men prioritizing their relationships and overall health and well-being over returning to pretreatment levels of function. Some unmet needs with regard to information about treatment schedules and side effects were reported, particularly among men with continuing functional symptoms. Conclusions These findings reinforce the importance of providing universal clear, concise, and timely information and supportive resources in the short term, and more targeted and detailed information and care in the longer term to maintain and improve treatment experiences for men undergoing EBRT.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Covariations between plant functional traits emerge from constraining parameterization of a terrestrial biosphere model - Marc Peaucelle; Cédric Bacour; Philippe Ciais; Nicolas Vuichard; Sylvain Kuppel; Josep Peñuelas; Luca Belelli Marchesini; Peter D. Blanken; Nina Buchmann; Jiquan Chen; Nicolas Delpierre; Ankur R. Desai; et al. (Global Ecology and Biogeography, 2019)
Aim The mechanisms of plant trait adaptation and acclimation are still poorly understood and, consequently, lack a consistent representation in terrestrial biosphere models (TBMs). Despite the increasing availability of geo‐referenced trait observations, current databases are still insufficient to cover all vegetation types and environmental conditions. In parallel, the growing number of continuous eddy‐covariance observations of energy and CO 2 fluxes has enabled modellers to optimize TBMs with these data. Past attempts to optimize TBM parameters mostly focused on model performance, overlooking the ecological properties of ecosystems. The aim of this study was to assess the ecological consistency of optimized trait‐related parameters while improving the model performances for gross primary productivity (GPP) at sites. Location Worldwide. Time period 1992–2012. Major taxa studied Trees and C 3 grasses. Methods We optimized parameters of the ORCHIDEE model against 371 site‐years of GPP estimates from the FLUXNET network, and we looked at global covariation among parameters and with climate. Results The optimized parameter values were shown to be consistent with leaf‐scale traits, in particular, with well‐known trade‐offs observed at the leaf level, echoing the leaf economic spectrum theory. Results showed a marked sensitivity of trait‐related parameters to local bioclimatic variables and reproduced the observed relationships between traits and climate. Main conclusions Our approach validates some biological processes implemented in the model and enables us to study ecological properties of vegetation at the canopy level, in addition to some traits that are difficult to observe experimentally. This study stresses the need for: (a) implementing explicit trade‐offs and acclimation processes in TBMs; (b) improving the representation of processes to avoid model‐specific parameterization; and (c) performing systematic measurements of traits at FLUXNET sites in order to gather information on plant ecophysiology and plant diversity, together with micro‐meteorological conditions.

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Developing an Integrated Ocean Observing System for New Zealand - Joanne O’Callaghan; Craig Stevens; Moninya Roughan; Chris Cornelisen; Philip Sutton; Sally Garrett; Giacomo Giorli; Robert O. Smith; Kim I. Currie; Sutara H. Suanda; Michael Williams; Melissa Bowen; et al. (Frontiers in Marine Science, 2019)

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Environmental evidence for a pygmy blue whale aggregation area in the Subtropical Convergence Zone south of Australia - Maria I. Garcia‐Rojas; K. Curt S. Jenner; Peter C. Gill; Micheline‐Nicole M. Jenner; Alicia L. Sutton; Robert D. McCauley (Marine Mammal Science, 2018)
The importance of the Subtropical Convergence Zone south of Australia as a feeding area to the pygmy blue whale of the eastern Indian Ocean was investigated to better understand migration patterns and habitat use. A combination of satellite tagging studies during 2003–2005 and acoustic and visual surveys during the austral summer of 2013 confirmed the presence of pygmy blue whales in the Subtropical Convergence Zone and provided evidence for feeding throughout the region. Of the 67 pygmy blue whales acoustically detected, many were localized in proximity to sea surface temperature fronts and high chlorophyll concentrations, which could be a behavioral strategy to attract conspecifics to good feeding sites. Aggregations of up to four pygmy blue whales, along with decreased call rates during the day, may suggest feeding despite no direct observations of pygmy blue whales consuming euphausiids. The oceanographic features present throughout the Subtropical Convergence Zone continue to create an environment productive enough to support the world's largest living mammals during their migratory foraging movements between the Southern Ocean and Indonesia.

An assessment of age and growth of violet cod (Antimora rostrata) in the Ross Sea, Antarctica - Peter L. Horn; Colin P. Sutton (Polar Biology, 2015)

New tools to boost butterfly habitat quality in existing grass buffer strips - Robin J. Blake; Ben A. Woodcock; Duncan B. Westbury; Peter Sutton; Simon G. Potts (Journal of Insect Conservation, 2011)

Comparison of microbial communities in pilot-scale bioreactors treating Bayer liquor organic wastes - Naomi J. McSweeney; Jason J. Plumb; Amanda L. Tilbury; Hugh J. Nyeboer; Matt E. Sumich; Anthony J. McKinnon; Peter D. Franzmann; David C. Sutton; Anna H. Kaksonen (Biodegradation, 2011)

The N-glycolyl form of mouse sialyl Lewis X is recognized by selectins but not by HECA-452 and FH6 antibodies that were raised against human cells - Junya Mitoma; Tatsuo Miyazaki; Mark Sutton-Smith; Misa Suzuki; Hideo Saito; Jiunn-Chern Yeh; Takehiro Kawano; Ole Hindsgaul; Peter H. Seeberger; Maria Panico; Stuart M. Haslam; Howard R. Morris; et al. (Glycoconjugate Journal, 2009)

Uncertainties in the relationship between atmospheric nitrogen deposition and forest carbon sequestration - MARK A. SUTTON; DAVID SIMPSON; PETER E. LEVY; ROGNVALD I. SMITH; STEFAN REIS; MARCEL Van OIJEN; WIM De VRIES (Global Change Biology, 2008)
In a recent study, Magnani et al. report how atmospheric nitrogen deposition drives stand‐lifetime net ecosystem productivity (NEP av ) for midlatitude forests, with an extremely high C to N response (725 kg C kg −1 wet‐deposited N for their European sites). We present here a re‐analysis of these data, which suggests a much smaller C : N response for total N inputs. Accounting for dry, as well as wet N deposition reduces the C : N response to 177 : 1. However, if covariance with intersite climatological differences is accounted for, the actual C : N response in this dataset may be et al. Multisite regression of simulated NEP av vs. total N deposition reproduces a high C : N response (149 : 1). However, once the effects of intersite climatological differences are accounted for, the value is again found to be much smaller, pointing to a real C : N response of about 50–75 : 1.

Macroinvertebrate community response to large-woody debris additions in small warmwater streams - Peter J. Hrodey; Bryan J. Kalb; Trent M. Sutton (Hydrobiologia, 2008)

Fine mapping and targeted SNP survey using rice-wheat gene colinearity in the region of the Bo1 boron toxicity tolerance locus of bread wheat - Thorsten Schnurbusch; Nicholas C. Collins; Russell F. Eastwood; Tim Sutton; Steven P. Jefferies; Peter Langridge (Theoretical and Applied Genetics, 2007)

Identification of transposons, retroelements, and a gene family predominantly expressed in floral tissues in chromosome 3DS of the hexaploid wheat progenitor Aegilops tauschii - Ryan Whitford; Ute Baumann; Tim Sutton; Luke Gumaelius; Petra Wolters; Scott Tingey; Jason A. Able; Peter Langridge (Functional & Integrative Genomics, 2006)

Accurately measuring volcanic plume velocity with multiple UV spectrometers - Glyn Williams-Jones; Keith A. Horton; Tamar Elias; Harold Garbeil; Peter J. Mouginis-Mark; A. Jeff Sutton; Andrew J. L. Harris (Bulletin of Volcanology, 2006)

Real-time measurement of volcanic SO2 emissions: validation of a new UV correlation spectrometer (FLYSPEC) - Keith A. Horton; Glyn Williams-Jones; Harold Garbeil; Tamar Elias; A. Jeff Sutton; Peter Mouginis-Mark; John N. Porter; Steven Clegg (Bulletin of Volcanology, 2006)

Bacterial degradation of arsenobetaine via dimethylarsinoylacetate - Richard O. Jenkins; Alisdair W. Ritchie; John S. Edmonds; Walter Goessler; Nathalie Molenat; Doris Kuehnelt; Christopher F. Harrington; Peter G. Sutton (Archives of Microbiology, 2003)

A computer image analysis system for microvessel density measurement in solid tumours - Jonathan Charles Goddard; Christopher Derek Sutton; Peter N. Furness; Roger Clive Kockelbergh; Kenneth John O'Byrne (Angiogenesis, 2002)

Associative search network: A reinforcement learning associative memory - Andrew G. Barto; Richard S. Sutton; Peter S. Brouwer (Biological Cybernetics, 1981)